Positive Psychology in Lifestyle Medicine and Health Care: Strategies for Implementation. Issue 5 (September 2019) - Lianov, Liana S.; Fredrickson, Barbara L.; Barron, Carrie; Krishnaswami, Janani; Wallace, Anne
Prevention and treatment of lifestyle-related diseases are realized through leading a healthy lifestyle. Activities supporting positive psychology can facilitate healthy behaviors and improve physiological health. Adding such activities to clinical care promotes attainment of the physical, social, and emotional elements of health, as defined by the World Health Organization—leading to (1) prolonged lifespan and quality of life, (2) lowered costs of care, and (3) reduced rates of provider burnout. A key challenge remains the translation of positive psychology–based practices into practical, implementable strategies by health care providers. An essential step is collaboration of positive psychology and health care researchers and practitioners to develop standards, terms, and measures and arrive at evidence-based clinical approaches addressing total well-being. The first Summit on Happiness Science in Healthcare enabled national experts and stakeholders in lifestyle medicine, medical education, health care administration, psychology, and community welfare to convene and identify best practices for practical implementation of positive psychology science into health care. This article draws on the summit discussions to address the gap between positive psychology theory and practical implementation in health care. We briefly summarize the positive psychology–health outcomes relationship and present key strategies needed to bridge this gap.